Study protocol of EMPOWER Participatory Action Research (EMPOWER-PAR): a pragmatic cluster randomised controlled trial of multifaceted chronic disease management strategies to improve diabetes and hyp - Ramli, Anis S.; Lakshmanan, Sharmila; Haniff, Jamaiyah; Selvarajah, Sharmini; Tong, Seng Fah; Bujang, Mohamad Adam; Abdul Razak, Suraya; Shafie, Asrul Akmal; Lee, Verna K.M.; Abdul Rahman, Thuhairah H.; Daud, Maryam H.; Ng, Kien K.; et al. (BioMed Central, 2014)
Background Chronic disease management presents enormous challenges to the primary care workforce because of the rising epidemic of cardiovascular risk factors. The chronic care model was proven effective in improving chronic disease outcomes in developed countries, but there is little evidence of its effectiveness in developing countries. The aim of this study was to evaluate the effectiveness of the EMPOWER-PAR intervention (multifaceted chronic disease management strategies based on the chronic care model) in improving outcomes for type 2 diabetes mellitus and hypertension using readily available resources in the Malaysian public primary care setting. This paper presents the study protocol. Methods/Design A pragmatic cluster randomised controlled trial using participatory action research is underway in 10 public primary care clinics in Selangor and Kuala Lumpur, Malaysia. Five clinics were randomly selected to provide the EMPOWER-PAR intervention for 1 year and another five clinics continued with usual care. Each clinic consecutively recruits type 2 diabetes mellitus and hypertension patients fulfilling the inclusion and exclusion criteria over a 2-week period. The EMPOWER-PAR intervention consists of creating/strengthening a multidisciplinary chronic disease management team, training the team to use the Global Cardiovascular Risks Self-Management Booklet to support patient care and reinforcing the use of relevant clinical practice guidelines for management and prescribing. For type 2 diabetes mellitus, the primary outcome is the change in the proportion of patients achieving HbA1c < 6.5%. For hypertension without type 2 diabetes mellitus, the primary outcome is the change in the proportion of patients achieving blood pressure < 140/90 mmHg. Secondary outcomes include the proportion of patients achieving targets for serum lipid profile, body mass index and waist circumference. Other outcome measures include medication adherence levels, process of care and prescribing patterns. Patients’ assessment of their chronic disease care and providers’ perceptions, attitudes and perceived barriers in care delivery and cost-effectiveness of the intervention are also evaluated. Discussion Results from this study will provide objective evidence of the effectiveness and cost-effectiveness of a multifaceted intervention based on the chronic care model in resource-constrained public primary care settings. The evidence should instigate crucial primary care system change in Malaysia.